The Correlation Between Anemia and Abortion in Pregnant Women - Ardika Desi Regita Tejowati; Wisnu Prabowo; Eric Edwin Yuliantara; Supriyadi Hari Respati (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2026)
Background: Anemia in pregnancy can occur when the hemoglobin concentration is less than normal so that oxygen binding cannot occur optimally. Insufficient oxygen supply for the mother's metabolism can indirectly affect both the mother and the fetus. Anemia in pregnancy can increase the risk of abortion. In 2021, there were 7,389 maternal deaths, one of which was caused by abortion. This study aims to determine whether there is an increased risk of abortion in pregnant women with anemia.Method: Analytical observational study using a case-control design with a ratio of case group and control group of 1:2. This study collected data from 52 subjects of pregnant women with abortion as the case group and 104 subjects of pregnant women with vaginal delivery as the control group during the period from January 2021 to December 2023. Subjects were determined based on inclusion and exclusion criteria using purposive sampling. The analysis of univariate and bivariate employed chi-square test; and as multivariate analysis the study employed logistic regression test.Result: Pregnant women with anemia have 2.67 times higher risk of experiencing abortion compared to pregnant women without anemia and this was a statistically significant (OR= 2.67; 95% CI= 1.31 to 5.49; p=0.007). In addition, there was a confounding variable of maternal age (OR= 3.03; 95% CI= 1.36 to 5.74; p=0.007) and gravidity (OR= 2.48; 95% CI= 1.19 to 5.19; p=0.015)Conclusion: There is a significant correlation between anemia and abortion in pregnant women.